In silico drug repurposing for potential HPV-induced skin wart treatment − A comparative transcriptome analysis - Navid Kashani; Amir Sabbaghian; Khadijeh Ahmadi; Mahdi Aalikhani (Journal of Genetic Engineering and Biotechnology)
Introduction: Warts are dermal disorders resulting from HPV infection and can be transmitted by direct contact. Existing treatment approaches, such as topical treatment with salicylate, have low efficiency and demonstrate side effects. Thus, the discovery of potent drug treatments for skin warts is necessary. Here we propose the use of alternative medications for the possible treatment of skin warts with the help of comparative transcriptome analysis and drug repurposing approaches. Methods: Gene expression datasets related to HPV-induced warts and cervical cancer were extracted from the GEO database. Differentially expressed genes (DEGs) were identified using DESeq2 in the Galaxy database. Upregulated DEGs were assessed for druggability using the DGIdb tool. Gene ontology and enrichment analysis were performed to investigate the characteristics of druggable DEGs. A molecular docking virtual screening was conducted using PyRx software to identify potential therapeutic targets for skin warts. The interactions between selected drug candidates and the target protein were analyzed using the BIOVIA Discovery Studio. The physicochemical characteristics of potential pharmaceuticals were evaluated using the SwissADME database. Finally, the molecular dynamics (MD) simulation was performed to validate the stability and dynamic behavior of drug-protein interactions. Results: Based on the findings from gene expression profiling, Integrin Alpha-X (ITGAX, CD11c) has been identified as a candidate protein that is significantly upregulated in individuals afflicted with skin warts. Integrin Alpha-X plays a crucial role in mediating intercellular interactions during inflammatory processes and notably enhances the adhesion and chemotactic activity of monocytes. Through molecular docking, MD, and physicochemical analyses, it has been demonstrated that dihydroergotamine effectively inhibits the ITGAX protein, suggesting its potential as a therapeutic agent for the management of skin warts. Conclusion: Dihydroergotamine can be repurposed as a potential drug in the treatment of skin warts by targeting Integrin Alpha-X protein.